The Application of Cyclone Ventilator Modification for Indoor Air Sanitation (Medico Legal Update, 2019)
There was a need to conduct research on the trial use of cyclone ventilator modification using active carbon as CO adsorbent in an indoor area so that its air fulfills the indoor air sanitation condition. This research was intended to put on cyclone ventilator modification to reduce the temperature, humidity, CO gas level and PM10 dust in indoor area so it can fulfill indoor health sanitation standard. The research used One Group Pretest Posttest Design. Cyclone ventilator modification could reduce indoor mechanic temperature by 10.919% in average, air humidity in average by 28.64%. The ability to reduce CO gas level was 28.65% in average and PM10 dust for about 52.80% after 2 hours the instrument works. Cyclone ventilator modification takes 2 hours to reduce temperature, humidity, CO gas level, and PM10 dust accumulated for 4 hours inside of mechanical room. Cyclone ventilator modification worked effectively operated inside of the room with 115.6m 3 volume and was able to create a quality standard circumstances. The performance of Cyclone Ventilator Modification as an air sanitation instrument can be evaluated from energy and economical aspect in general. Secondly, those aspects shows that indoor air sanitation instrument can only works (moves) using the wind breeze.